Chemical Investigation and Antimicrobial Activity of Medicinal Plant Toddalia asiatica Lam - Wilmar Maarisit; Misran Lawani (Indonesian Journal of Chemistry, 2020)
Medicinal plants have become important sources of natural products, which have been used in the development of therapeutic agents. Four new coumarins (1-4) have been isolated together with five known metabolites (5-9) from the medicinal plant T. asiatica. The structures of 1-9 were assigned based on their spectroscopic data. Compounds (1-9) inhibited the growth of the Gram-negative bacteria E. coli and Gram-positive bacteria S. aureus at a concentration of 25 and 50 μg/disc. Compounds (2-4) inhibited the phytopathogenic fungus C. cucurbitarum at 50 μg/disc.